Interdisciplinary approach in development and implementation of local guideline for surgical antimicrobial prophylaxis: Experience of the university hospital 'Tsaritsa Yoanna - ISUL', Sofia, Bulgaria - Petrov Andrey; Gatchev Emil; Damyanov Damyan; Korukov Boyko; Kolev Emil (Srpsko lekarsko drustvo, 2014)
Objective Surgical antimicrobial prophylaxis (SAP) is a method proved to be effective in reducing the risk of surgical site infections (SSI). Although there are numerous international and local Guidelines, SAP is often performed inappropriately. The monitoring that was carried out at the Surgery Clinic of the University Hospital 'Tsaritsa Yoanna - ISUL' in August 2008 showed a high level of inappropriately performed SAP. In order to optimize SAP, a Local Guideline (LG) for SAP was developed. Methods LG for SAP was developed and implemented using the interdisciplinary approach, on the basis of internationally accepted standards of SAP, taking into account the specifics of the hospital. Monthly monitoring of the level of compliance of SAP with the LG for SAP was carried out. The use of antimicrobial agents (AMA) at the Clinic was reported using the DDD/100 patient day method. Results Three months after the LG implementation, the rate of appropriately performed SAP increased from 5% to 40% and at the end of 2009 even to 92%. The AMA usage in 2009 was reduced by nearly 26%: from total of 58.71 DDD/100 patient days in 2008 to 43.45 DDD/100 patient days and total AMA costs were reduced by more than 31%: from € 29.764 in 2008 to € 20.300 in 2009. Conclusions The interdisciplinary approach in the development and implementation of LG for SAP led to SAP optimization at the Surgery Clinic, significant reduction in AMA usage and considerable savings of financial resources.